2017
DOI: 10.1016/j.ecoser.2016.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of green space dynamics on urban heat islands: Mitigation and diversification

Abstract: A B S T R A C TUnderstanding how green spaces affect urban temperature is crucial for assessing thermal benefits of landscape planning. This study investigated green space dynamics and land surface temperature (LST) in the Beijing metropolis. Landscape types were classified from QuickBird (2002) ). (2) LST change was not significant in the unchanged (0-0.19°C) and exchanged green space (in the range of −0.02-0.25°C). However, there were minor decreases of LST in areas of green expansion (in the range of −1.11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
85
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(98 citation statements)
references
References 47 publications
10
85
0
3
Order By: Relevance
“…Moreover, it was noteworthy that, although the Green landscape transformed into Grey landscape led to an LST increase, the transformation of Grey landscape into Green landscape did not achieve a significant cooling effect (the median ∆LST was near 0). The warming effect resulting from green space reduction was greater than the cooling effect resulting from a green space increase, consistent with the conclusions of Sun and Chen [20]. Generally speaking, the temperature change resulting from different landscape transformations is not linearly reversible.…”
Section: Land Surface Temperature Change Resulting From Landscape Trasupporting
confidence: 87%
See 2 more Smart Citations
“…Moreover, it was noteworthy that, although the Green landscape transformed into Grey landscape led to an LST increase, the transformation of Grey landscape into Green landscape did not achieve a significant cooling effect (the median ∆LST was near 0). The warming effect resulting from green space reduction was greater than the cooling effect resulting from a green space increase, consistent with the conclusions of Sun and Chen [20]. Generally speaking, the temperature change resulting from different landscape transformations is not linearly reversible.…”
Section: Land Surface Temperature Change Resulting From Landscape Trasupporting
confidence: 87%
“…It can be concluded that the number of green spaces is not the only criterion that should be assessed for temperature mitigation. This study corroborated the opinion of Sun and Chen [20] who pointed out that the "ecosystem services of temperature mitigation were not equal between the loss and gain of green spaces even within the same area". Besides controlling the city's total number of green spaces through urban planning, other indicators should be introduced.…”
Section: Uncertainties Of Landscape Types Interpretation and Land Sursupporting
confidence: 89%
See 1 more Smart Citation
“…The cooling effect of urban green space is regarded as an ecosystem regulating service [9,10]. However, rapid urbanization leads to a significant transformation of green space to impervious surface, urbanization profoundly influences biodiversity and ecosystem function; one of the ecological consequences of urbanization is the urban heat island (UHI) effect [11]. This phenomenon is particularly serious in the rapidly growing cities in China [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Such high dynmism could potentially influence the quality of UG and thereby ecosystem services ( Zhou et al 2017a). For example, the newly created UG patches may have lower quality than the currently/ previously existing ones (Wang et al 2019), and provide less ecosystem services (Sun and Chen 2017). This warrants further research in the future.…”
Section: The Implications Of Urban Planning and Managementmentioning
confidence: 99%